Extracellular matrix from decellularized porcine organs as scaffolds for insulin-secreting cells and pancreatic islets - Dhandapani, Vignesh; Boabekoa, Pakindame; Vermette, Patrick (Frontiers in Endocrinology, 2026)
Extracellular Matrix (ECM) from different organs has been used to cultivate several cell types. ECM produced by organ decellularization contains collagens, fibronectin, glycosaminoglycans (GAGs), laminins and other components essential in providing structural support and biochemical cues for cells to attach, function, and proliferate. The organ from which ECM is extracted and produced is hypothesized to play a vital role in cell responses upon recellularization. To investigate this hypothesis, five porcine organs (bladders, kidneys, livers, lungs, and pancreas) were decellularized by a detergent-based method or by detergent-free procedures. Insulin-secreting rat pancreatic β-like cells (INS-1) were first used to screen, over 7 days, the effect of the ECM produced by the tested decellularization techniques from the five selected organs, revealing SDS treatment did not result in cell responsive ECMs for all the tested organs. Detergent-free-derived ECMs, on the other hand, allow cell attachment except for the pancreatic ECM. The biocompatibility of the ECMs made from detergent-free methods was subsequently validated using cell proliferation and cell metabolism assays, immunostaining for insulin and actin expression, as well as glucose-stimulated insulin secretion (GSIS). INS-1 cells proliferated on certain detergent-free ECMs and secreted insulin following 7 days of culture. Further, primary pancreatic mouse islets were isolated and cultivated 48 hours on detergent-free decellularized bladder pieces and histological analysis showed intact islets embedded within the bladder ECM. GSIS revealed functional islets following 48 hours on detergent-free-derived bladder ECM. Islets cultivated on detergent-free-derived bladder ECM expressed insulin, with endothelial cells (i.e., CD31-positive cells) localized at the islet-ECM interface.